2022
DOI: 10.1103/physrevd.106.042006
|View full text |Cite
|
Sign up to set email alerts
|

Accurate modeling and mitigation of overlapping signals and glitches in gravitational-wave data

Abstract: The increasing sensitivity of gravitational-wave detectors has brought about an increase in the rate of astrophysical signal detections as well as the rate of "glitches"; transient and non-Gaussian detector noise. Temporal overlap of signals and glitches in the detector presents a challenge for inference analyses that typically assume the presence of only Gaussian detector noise. In this study we perform an extensive exploration of the efficacy of a recently proposed method that models the glitch with sine-Gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 128 publications
(189 reference statements)
0
12
1
Order By: Relevance
“…As BayesWave uses an MCMC to marginalize over the parameters, the end result is a posterior distribution of time series of the glitch, g(t). To actually perform the glitch mitigation, we select a fair draw from the posterior [31] by randomly selecting a single sample from the posterior, and subtract it from the detector data. The timescale to model glitches and produce glitch-subtracted data using BayesWave is up to multiple days depending on the type of glitch that is being analysed [30].…”
Section: Glitch Subtraction Using Waveletsmentioning
confidence: 99%
See 4 more Smart Citations
“…As BayesWave uses an MCMC to marginalize over the parameters, the end result is a posterior distribution of time series of the glitch, g(t). To actually perform the glitch mitigation, we select a fair draw from the posterior [31] by randomly selecting a single sample from the posterior, and subtract it from the detector data. The timescale to model glitches and produce glitch-subtracted data using BayesWave is up to multiple days depending on the type of glitch that is being analysed [30].…”
Section: Glitch Subtraction Using Waveletsmentioning
confidence: 99%
“…Scattered light glitches are a known challenge for BayesWave. Recent investigations [31] have shown that in order to fully model scattered light glitches with BayesWave, low-SNR wavelets must be used. These investigations also find that wavelets at the required SNRs are strongly disfavoured when using priors similar to those used by the analyses discussed in this work.…”
Section: Eventmentioning
confidence: 99%
See 3 more Smart Citations